Recommendations of national work conferences on teacher education an identification of implementation measures and impediments to implementation - Senora, Ludivina R. 1928- (s.n.], 1966)
This study presents a content analysis of the recommendations of the seven national work conferences on teacher education from 1956 to 1964. The purpose of which is to find out what has been done in their implementation and to identify reasons for the non-implementation of these suggestions made during the conferences.